(untitled) (PerCursos, 2024)
An interpretation of the Brazilian reality from the context of the southern region of the country takes into account the socioeconomic, cultural, and political markers that constitute this territory, as well as the specific strategies developed by the black population to continue the historic struggle for a life with dignity in Brazil. It is in this historical and geographical context that Afro-popular formation developed. Despite considering the collective nature of this process, like everything built by and for social movements, there are protagonists who led the actions based on their militant practices. The choice of Professor Jeruse Romão among this group active in Santa Catarina since the 1980s is due to her recognition as a reference by activists and intellectuals of the Brazilian black movement. With this article, my main motivation is to highlight the relevance of Professor Jeruse Romão’s trajectory not only for the black movement but, especially, for Brazilian education. Thus, my objective is to characterize the educational practices of Afro-popular education based on black thought in the counter-colonial process of building public policies at the service of social justice. I believe that this movement has special relevance in confronting the invisibility of the black population in the South of Brazil, which not only exists and resists but actively organizes and articulates other possibilities of existence beyond a racist society.